The value potential of the book in forming the future image - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2023)
The article reveals the value potential of the book, its role in choosing the life path of young people, shaping their lifestyle, overcoming new global challenges and risks. The way out is seen in the development of national cultures, which form a new convergent world in a natural dialogue. This world is the basis of stability, progress and safe life on Earth. A breakthrough to the new is most often associated with the development of inheritance system, preservation and transmission of identification peoples’ features that are preserved in the cultural code, a reboot of the spiritual matrix of a transforming society, with the renewal of its value bases. The problems of coding, studying the problems of digitalisation, the development of all types of communications, and the introduction of new information technologies are being updated with the development of the information society. The book appears in this case to some extent as a carrier of encoded information, a sign-symbolic form of a cultural code, being an important link in the mechanism of intergenerational continuity of spiritual and moral development. The social life of a person, including that which is reflected in literature, in a book, is the soil, where values are renewed, filled with new meaning, enriched or rejected. Concrete measures are proposed to popularise the book, form a book culture, and improve the work of the book infrastructure.